How To Measure Knocking Intensity In Dual-Fuel Internal Combustion Engines : A Review - Santoso, Dany (Institut Teknologi Sepuluh Nopember, 2025)
Internal combustion engines (ICE), especially diesel engines, require additional (secondary) fuel to improve their gas emissions. The selection of hydrogen as a secondary fuel in a diesel dual fuel (DDF) system is meaningful because it does not contain carbon to support exhaust gas decarbonization. Hydrogen also has a high calorific value, which can be a threat of knocking in the engine during operation. Early detection of knocking can prevent further damage to the piston and cylinder. Experts apply pressure and frequency calculations to measure the intensity of knocking. The results obtained in a homogeneous charge compression ignition (HCCI) engine were that slight knocking occurred at a hydrogen-air ratio above 0.3, and heavy knocking rose at a hydrogen-air ratio of 0.45.